A Prospective Study of the Association Between Plasma Calprotectin Levels and New-Onset CKD in the General Population - Arno R. Bourgonje; Martin F. Bourgonje; Sacha la Bastide-van Gemert; Tom Nilsen; Clara Hidden; Ron T. Gansevoort; Douwe J. Mulder; Jan-Luuk Hillebrands; Stephan J.L. Bakker; Robin P.F. Dullaart; Harry van Goor; Amaal E. Abdulle (Kidney International Reports)
Introduction: Systemic inflammation has been associated with chronic kidney disease (CKD). In this study, we aimed to investigate a potential association between the plasma biomarker of inflammation calprotectin and new-onset CKD in a population-based cohort study. Methods: Individuals without CKD at baseline (n = 4662) who participated in the Prevention of REnal and Vascular ENd-stage Disease (PREVEND) prospective population-based cohort study in the Netherlands were included. Baseline plasma calprotectin levels were assessed in samples that had been stored at −80 °C. Occurrence of new-onset CKD was defined as a composite outcome of an estimated glomerular filtration rate (eGFR) <60 ml/min per 1.73 m2, urinary albumin excretion (UAE) >30 mg/24h, or both. Results: Baseline median (interquartile range) plasma calprotectin levels were 0.49 (0.35–0.68) mg/l and baseline median eGFR was 95.9 (interquartile range: 85.0–105.7) ml/min per 1.73 m2. After median follow-up of 8.3 (7.8–8.9) years, 467 participants developed new-onset CKD. Baseline plasma calprotectin levels were significantly associated with an increased risk of new-onset CKD (hazard ratio [HR] per doubling 1.28 [95% confidence interval, CI: 1.14–1.44], P < 0.001), independent of potentially confounding factors (HR 1.14 [95% CI: 1.01–1.29], P = 0.034), except for baseline high-sensitive C-reactive protein (hs-CRP) (HR 1.05 [0.91–1.21], P = 0.494). In secondary analyses, the association between plasma calprotectin and occurrence of UAE >30 mg/24h remained significant (HR 1.17 [1.02–1.34], P = 0.027), but not significantly so for the incidence of eGFR <60 ml/min per 1.73 m2 as individual outcome (HR 1.15 [0.92–1.43], P = 0.218). Conclusion: Higher plasma calprotectin levels are associated with an increased risk of developing CKD in the general population. This association is mitigated after adjustment for hs-CRP, and more pronounced with new-onset CKD defined by UAE.